If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = -1x + -3 Reorder the terms: 2 + 4x = -1x + -3 Reorder the terms: 2 + 4x = -3 + -1x Solving 2 + 4x = -3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + 4x + x = -3 + -1x + x Combine like terms: 4x + x = 5x 2 + 5x = -3 + -1x + x Combine like terms: -1x + x = 0 2 + 5x = -3 + 0 2 + 5x = -3 Add '-2' to each side of the equation. 2 + -2 + 5x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -3 + -2 5x = -3 + -2 Combine like terms: -3 + -2 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 5x-2(4-x)=20 | | 0.5x*(12x^3+6x^2-2x)=4 | | 4(-2x+5)=-6 | | X+2=4x+5 | | x^2+18x+77=0 | | -6x-6=18 | | 4(x+18)=788 | | 9x-3(2x-4)=15 | | 5x-13-3x-19=-6 | | -8=-17+0-14 | | 5x-13-3c-19=-6 | | 2x-7(3+x)=x+3 | | 16-3x=4+x | | 7-12(3+x)=31 | | 7x-(x-1)=25 | | 2x=6+3y | | 10x+4=4x-9 | | y=x^2+6x+10 | | .50(2n-5)=4n-1 | | 3x-(2x-7)=15 | | 5(x-3)-4(x+2)=2+3(1-2x) | | -5x+7+7x=6 | | 4+2x=-2 | | 12x^3+6x^2-2x=4 | | 4(y-6x)=12 | | -9m+7-3+1+m-5= | | 3(x-1)=2x+3 | | 12x^2-3x-9=0 | | 4x+24=-4 | | (9-2i)(4+7i)= | | 5v^2-7v=1 | | 44-c=26 |